2016
DOI: 10.1002/ejlt.201600201
|View full text |Cite
|
Sign up to set email alerts
|

Physical and sensory properties of chocolate made with lecithin of different origin

Abstract: The development of genetically modified foods, but also the use of therefrom produced ingredients in food manufacturing raises uncertainties and concerns in both producers and consumers. Lecithin from soy beans, which is most frequently used to modify the flow behavior of chocolate masses, is a prominent example of such an ingredient. In this study, lecithin of different origin, namely from soy bean, sunflower, or canola seeds, was incorporated into lecithin‐free masses of white and milk chocolate. The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Numerous studies have attempted to describe the emulsifiers and their concentrations; however, the specific relationship between them and color properties remains unknown. In a study performed by Böhme et al (2016), the effect of lecithin addition on product color was found to be significant in white chocolate, while it was detected as negligible for milk chocolate. In the study, it was concluded that the difference between the control and white chocolate samples containing different originated lecithin was within the range to allow visual discrimination according to the data in the color measurement analysis.…”
Section: Effect Of Emulsifiers On Colormentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous studies have attempted to describe the emulsifiers and their concentrations; however, the specific relationship between them and color properties remains unknown. In a study performed by Böhme et al (2016), the effect of lecithin addition on product color was found to be significant in white chocolate, while it was detected as negligible for milk chocolate. In the study, it was concluded that the difference between the control and white chocolate samples containing different originated lecithin was within the range to allow visual discrimination according to the data in the color measurement analysis.…”
Section: Effect Of Emulsifiers On Colormentioning
confidence: 98%
“…On the other hand, the color of the emulsifier may vary depending on the type, the source, and the production technique. For instance, crude lecithin is a viscous liquid with a color ranging from light yellow to brown (Pires et al, 2017), while PGPR, a highly viscous liquid, is defined as light brown in color (Mortensen, Aguilar, Crebelli, Di Domenico, Dusemund, et al, 2017), AMPs are appeared as a yellowish to light brown liquid material (Norn, 2015), According to the study of Böhme et al (2016), it was determined that there were differences in the L* values of white chocolates due to the different content of coloring compounds used in the preparation of commercial lecithins. In this respect, it should be taken into account that lecithin addition may affect the color perception expected from chocolate products, especially in white chocolate even if used in low amounts during production.…”
Section: Effect Of Emulsifiers On Colormentioning
confidence: 99%
“…Emulsifiers can also be used to reduce particle interactions and are added to control the rheological properties of molten chocolate. 22,35 The common theory behind their mode of action is based on the adsorption of their polar head group to the polar particle surface of sugar, with the fatty acid moieties oriented away from the surface towards the continuous fat phase. 36 This, conceptually, is similar to how certain emulsifiers can stabilize water-in-oil emulsions, where the dispersed polar aqueous phase is analogous to dispersed polar sugar or cocoa solids.…”
Section: Emulsifiersmentioning
confidence: 99%